Changes in chlamydia control activities in Europe between 2007 and 2012: a cross-national survey. - van den Broek, Ingrid V; Sfetcu, Otilia; van der Sande, Marianne A; Andersen, Berit; Herrmann, Björn; Ward, Helen; Götz, Hannelore M; Uusküla, Anneli; Woodhall, Sarah C; Redmond, Shelagh M; Amato-Gauci, Andrew J; Low, Nicola; et al. (European journal of public health, 2015)
In 2012, the levels of chlamydia control activities including primary prevention, effective case management with partner management and surveillance were assessed in 2012 across countries in the European Union and European Economic Area (EU/EEA), on initiative of the European Centre for Disease Control (ECDC) survey, and the findings were compared with those from a similar survey in 2007.